2023
DOI: 10.52711/0974-360x.2023.00067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CRP, IL-6, Leukocytes, NLR on Chronic Periodontitis in Acute Coronary Syndrome

Abstract: Chronic periodontitis is associated with coronary heart disease (CHD), including Acute Coronary Syndrome (ACS), which causes inflammation. CRP, IL-6, leukocytes, neutrophils, and lymphocytes are inflammatory mediators. This study aimed to evaluate CRP, IL6, leukocytes, and NLR effect on chronic periodontitis in ACS patients. A total of 60 ACS patients who underwent coronary angiography were used in this study. Coronary artery assessment was measured based on QCA coronary angiography. Periodontal status measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Due to the high reactivity of ROS molecules, cells can generate scavenger molecules and antioxidants that maintain redox homeostasis by upregulating genes involved in oxidative stress reduction. ROS molecules induce the expression of proinflammatory proteins by activating various transcription factors, including NF-κB [6]. Following HBO exposure, ROS molecules modify adaptive mechanisms that mitigate cell damage [3].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the high reactivity of ROS molecules, cells can generate scavenger molecules and antioxidants that maintain redox homeostasis by upregulating genes involved in oxidative stress reduction. ROS molecules induce the expression of proinflammatory proteins by activating various transcription factors, including NF-κB [6]. Following HBO exposure, ROS molecules modify adaptive mechanisms that mitigate cell damage [3].…”
Section: Resultsmentioning
confidence: 99%
“…MMP-12 also activates interferon-alpha (IFN-α), which contributes to the repair of endothelial dysfunction. In addition, MMP-12 can promote anti-inflammatory signals and suppress proinflammatory signals [6]. Previous research has identified potential protein targets for MMP-12, allowing it to exert its proteolytic activity on various protein substrates.…”
Section: Hypoxiamentioning
confidence: 99%